Measurement instruments to assess posture, gait, and balance in Parkinson's disease: Critique and recommendations. Issue 9 (4th March 2016) - Bloem, Bastiaan R.; Marinus, Johan; Almeida, Quincy; Dibble, Lee; Nieuwboer, Alice; Post, Bart; Ruzicka, Evzen; Goetz, Christopher; Stebbins, Glenn; Martinez‐Martin, Pablo; Schrag, Anette; ,
ABSTRACT: Background: Disorders of posture, gait, and balance in Parkinson's disease (PD) are common and debilitating. This MDS‐commissioned task force assessed clinimetric properties of existing rating scales, questionnaires, and timed tests that assess these features in PD. Methods: A literature review was conducted. Identified instruments were evaluated systematically and classified as "recommended, " "suggested, " or "listed." Inclusion of rating scales was restricted to those that could be used readily in clinical research and practice. Results: One rating scale was classified as "recommended" (UPDRS‐derived Postural Instability and Gait Difficulty score) and 2 as "suggested" (Tinetti Balance Scale, Rating Scale for Gait Evaluation). Three scales requiring equipment (Berg Balance Scale, Mini‐BESTest, Dynamic Gait Index) also fulfilled criteria for "recommended" and 2 for "suggested" (FOG score, Gait and Balance Scale). Four questionnaires were "recommended" (Freezing of Gait Questionnaire, Activities‐specific Balance Confidence Scale, Falls Efficacy Scale, Survey of Activities, and Fear of Falling in the Elderly–Modified). Four tests were classified as "recommended" (6‐minute and 10‐m walk tests, Timed Up‐and‐Go, Functional Reach). Conclusion: We identified several questionnaires that adequately assess freezing of gait and balance confidence in PD and a number of useful clinical tests. However, most clinical rating scales for gait, balance, and posture perform suboptimally or have been evaluated insufficiently. No instrument comprehensively and separately evaluates all relevant PD‐specific gait characteristics with good clinimetric properties, and none provides separate balance and gait scores with adequate content validity for PD. We therefore recommend the development of such a PD‐specific, easily administered, comprehensive gait and balance scale that separately assesses all relevant constructs. © 2016 International Parkinson and Movement Disorder Society